Prions: Some Details and Diseases - Yasir, Saif Jabbar; Al- Makhzoomy, Taghreed Abdul Kareem (Medical Science Journal for Advance Research, 2021)
Prion diseases or transmissible spongiform encephalopathies (TSEs) are a family of rare progressive neurodegenerative disorders that affect both humans and animals. They are distinguished by long incubation periods, characteristic spongiform changes associated with neuronal loss, and a failure to induce inflammatory response. Prion diseases in animals, Scrapie in sheep, chronic wasting disease (CWD) in deer, bovine spongiform encephalopathy (commonly known as "mad cow disease") in cattle, and Creutzfeldt-Jakob disease in humans are all examples of infectious diseases. The prion protein (PrP) was identified in a patient in 2015, and it was previously believed to be the cause of all known mammalian prion diseases. However, The protein alpha-synuclein, which is thought to be responsible for MSA, was suggested to be the cause of the disease in 2015.